Submassive and Massive Pulmonary Embolism: A Target for Thrombolytic Therapy? - Konstantinides, Stavros; Geibel, Annette; Kasper, Wolfgang (Thrombosis and Haemostasis, 1999)
Thrombolytic agents have been consistently demonstrated to dissolve pulmonary thrombi much more rapidly and effectively than heparin alone. Rapid resolution of pulmonary embolism (PE) is accompanied by a significant decrease in pulmonary artery pressure and an improvement in right ventricular function. However, it is no longer than 7 days until the findings of patients treated with heparin improve to a similar extent. Previous studies were not designed to determine whether this short-lasting difference in favor of thrombolysis can indeed affect the prognosis of patients with PE and thus justify the 1% (or even higher) risk of cerebral or fatal bleeding. Recently, two large registries demonstrated the importance of right ventricular dysfunction assessed by echocardiography as an independent predictor of mortality. Thrombolytic treatment was shown in one of these registries to be associated with a 50% reduction of death risk in clinically stable patients with right ventricular enlargement. It was thus possible to identify a group of patients with massive PE who are most likely to benefit from early thrombolysis. These findings now have to be confirmed by a prospective randomized trial which will compare thrombolysis with heparin alone in this high-risk patient population, focusing on clinical end points such as overall and event-free survival in the acute phase of PE.
Keywords: Pulmonary embolism; thrombolysis; prognosis; mortality